ANALISIS PERUBAHAN EKOSISTEM KAWASAN PESISIR PULAU SABANG - mustaqim mustaqim Abubakar (UNIVERSITAS SEBELAS MARET (UNS), 2018)
This research was intended to analyze the cause and impacts of the coastal ecosystem changes on the fishing community on Sabang island. The changes of coastal ecosystem of corals and mangroves were believed to have direct impacts to local communities who live on fishing in the island. Mix method approach such as survey, in-depth interviews, focus group discussions and observation was applied to collect the data. The results showed that those coastal ecosystem changes were caused by various communitie activities such as fish bombing, toxic materials, coral dredging, waste disposal, freshwater diversion and natural disaster such as tsunami. Therefore, changes in ecosystems have had serious impact on fishermen communities' activities. In addition, the most perceived impacts of recent years are reduced diversity of reef fish, further fishing range, declining marine biota population, and reduced mangrove areasKeywords: Ecosystems, Coastal Zones, Sabang IslandAbstrakPenelitian ini bertujuan untuk menganalisis penyebab dan dampak perubahan ekosistem pesisir terhadap masyarakat nelayan di Pulau Sabang. Perubahan ekosistem karang dan mangrove telah memiliki dampak langsung bagi masyarakat nelayan di Pulau Sabang. Pendekatan survei, wawancara mendalam, focus group discussion, dan observasi digunaan untuk mengumpulkan data. Hasilnya menunjukkan bahwa perubahan ekosistem pesisir tersebut disebabkan oleh berbagai kegiatan masyarakat seperti pengeboman ikan, penggunaan bahan beracun, pengerukan karang, pembuangan limbah, pengalihan air tawar dan bencana alam seperti tsunami. Perubahan ekosistem berdampak serius pada kegiatan masyarakat nelayan. Dampak yang paling dirasakan beberapa tahun terakhir adalah berkurangnya keragaman ikan karang, jangkauan penangkapan ikan lebih jauh, penurunan populasi biota laut, dan berkurangnya luasan mangrove.Kata Kunci: Ekosistem, Kawasan Pesisir, Pulau Sabang